3x-6+2x-6=10x-8

Simple and best practice solution for 3x-6+2x-6=10x-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6+2x-6=10x-8 equation:


Simplifying
3x + -6 + 2x + -6 = 10x + -8

Reorder the terms:
-6 + -6 + 3x + 2x = 10x + -8

Combine like terms: -6 + -6 = -12
-12 + 3x + 2x = 10x + -8

Combine like terms: 3x + 2x = 5x
-12 + 5x = 10x + -8

Reorder the terms:
-12 + 5x = -8 + 10x

Solving
-12 + 5x = -8 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-12 + 5x + -10x = -8 + 10x + -10x

Combine like terms: 5x + -10x = -5x
-12 + -5x = -8 + 10x + -10x

Combine like terms: 10x + -10x = 0
-12 + -5x = -8 + 0
-12 + -5x = -8

Add '12' to each side of the equation.
-12 + 12 + -5x = -8 + 12

Combine like terms: -12 + 12 = 0
0 + -5x = -8 + 12
-5x = -8 + 12

Combine like terms: -8 + 12 = 4
-5x = 4

Divide each side by '-5'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| -3x^2+8x+14=0 | | -14=2+4w | | 2(x-7)-6=-2(-7x+1)-4x | | 1.6x+x=130 | | 2x+14(x+1)=0 | | -110=-8z+2 | | -7(n+2)+16=-4n-4 | | 2x+14-(x-1)=0 | | 2*(x+i*y)=6-i*3 | | -4+y=41 | | 33-19=2(x-8) | | 6x-36+2=8x-8 | | 4x+15=16x-11 | | -2x^2-9x+14=0 | | 2x^2-x-6=y | | 6x+4=-2x-7 | | 6(5-X)=-2(X+43) | | 50m+42975=45450-175m | | b+25=-69 | | 2=5y+2 | | y-3=3/4(x-16) | | y/10=3/6 | | 6/9=y/12 | | log(8x-15)=2 | | 11x(12-x)-30=20x+59-6x(4x-13) | | 1/6+2/3+1/18=n | | 1/6+2/3+1/18= | | 3x-6y=-21 | | 90/95=n/19 | | 0.02/100 | | 12/14=n/7 | | Y^1/3*y^4/3 |

Equations solver categories